Mr. Keynes meets the classics: Government spending and the real exchange rate - Benjamin Born; Francesco D'Ascanio; Gernot J. Müller; Johannes Pfeifer (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2021)
In economies with fixed exchange rates, the adjustment to government spending shocks is asymmetric. A fiscal expansion appreciates the real exchange rate but does not stimulate output. A fiscal contraction does not alter the exchange rate, but lowers output. We develop these insights in a two-sector model of a small open economy with downward nominal wage rigidity. We establish new empirical evidence that supports the predictions of the model along several dimensions: not only does the exchange rate regime shape the fiscal transmission mechanism as predicted by the model - in doing so it also interacts with economic slack and inflation.
Keywords: E62; F41; F44; 330; Downward nominal wage rigidity; government spending shocks; exchangerate peg; real exchange rate; nonlinear effects; asymmetric adjustment; depreciation bias